Discursive Construction of Moral Boundaries in Anti-Immigration Demonstrations - Buraschi, Daniel; Aguilar-Idáñez, María-José (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2023)
The systematic violation of rights that characterizes migration management in the Canary Islands in recent years would not be possible without the existence of moral boundaries, symbolic lines of separation that exclude migrants from the space of moral obligation. The construction of moral boundaries is key to understanding how racism is legitimized in a liberal-democratic framework, justifying violence by appealing to values considered “democratic”. The discursive strategies of moral exclusion and the interpretative repertoires used by participants in the first anti-immigration demonstrations held in the Canary Islands are analyzed. Demonstrators moralize the rejection and justify the violation of migrants’ rights (including dying at sea) based on common sense and appealing to values such as equality and security. The discursive strategies are common, but the moral exclusion mechanism of threat is expressed in different interpretative repertoires (family vs. homeland) in each demonstration. All the discursive strategies identified moralize actions that would be unacceptable in another context.